READING LADDERS FOR HUMAN RELATIONS (Editor: Eileen Tway) - Booth, Philip (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1982)
Eileen Tway, Ed. READING LADDERS FOR HUMAN RELATIONS. (6th Edition). Urbana, Illinois: National Council of Teachers of English, 1981. 398 pp.